2022
DOI: 10.1101/2022.01.03.474792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality assessment of anatomical MRI images from Generative Adversarial Networks: human assessment and image quality metrics

Abstract: Background: Generative Adversarial Networks (GANs) can synthesize brain images from image or noise input. So far, the gold standard for assessing the quality of the generated images has been human expert ratings. However, due to limitations of human assessment in terms of cost, scalability, and the limited sensitivity of the human eye to more subtle statistical relationships, a more automated approach towards evaluating GANs is required. New method: We investigated to what extent visual quality can be assesse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…To further evaluate the difference among datasets from a quantitative perspective, we computed the Fréchet inception distance (FID) (Heusel et al, 2017) between each pair of datasets. FID is widely used in the GAN literature and is a popular metric for measuring the feature distance between two distributions, which also shows sensitivity to image quality and good correspondence with human perception (Treder et al, 2022). We randomly selected 200 samples of each dataset, took a representative slice (the central slice in the sagittal direction), and computed FID between the datasets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further evaluate the difference among datasets from a quantitative perspective, we computed the Fréchet inception distance (FID) (Heusel et al, 2017) between each pair of datasets. FID is widely used in the GAN literature and is a popular metric for measuring the feature distance between two distributions, which also shows sensitivity to image quality and good correspondence with human perception (Treder et al, 2022). We randomly selected 200 samples of each dataset, took a representative slice (the central slice in the sagittal direction), and computed FID between the datasets.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative to GANs, other methods using variational autoencoders (VAEs) (Kingma & Welling, 2013) have also been devised, such as Tudosiu et al (2020). However, it has been reported that GANs tend to produce clearer images than VAEs in diffusion‐weighted and T1‐weighted images (Treder et al, 2022). More recently, latent diffusion models have been proposed for generating synthetic images (Pinaya et al, 2022).…”
Section: Related Workmentioning
confidence: 99%